Mathematical analysis : differentiation and integration - Aramanovich, I. G. (Isaak Genrikhovich) (International series of monographs in pure and applied mathematics, v. 81., 1965)
Mathematical Analysis: Differentiation and Integration is devoted to two basic operations of mathematical analysis, differentiation and integration. The problems directly connected with the operations of differentiation and integration of functions of one or several variables are discussed, together with elementary generalizations of these operations. This volume is comprised of seven chapters and begins by considering the differentiation of functions of one variable and of n variables, paying particular attention to derivatives and differentials as well as their properties. The next chapter d.